2022
DOI: 10.1002/pan3.10419
|View full text |Cite
|
Sign up to set email alerts
|

Informing the design of urban green and blue spaces through an understanding of Europeans' usage and preferences

Abstract: 1. In light of global climate change and the biodiversity crisis, making cities more resilient through an adjusted design of urban green and blue spaces is crucial.Nature-based solutions help address these challenges while providing opportunities for nature experiences, and providing cultural ecosystem services that support public health. The COVID-19 pandemic and its associated stressors highlighted the interrelated socio-ecological services provided by nature-based solutions like urban green and blue spaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Individuals visit urban riversides primarily for physical exercise, recreation and leisure, including activities such as walking or jogging, cycling, swimming, dancing, skateboarding, rowing, dragon boat racing, water marathons, dog walking, picnicking, dining, photography, social gatherings, commuting, chess, and camping (e.g., Chen & Ma, 2023;Gargiulo et al, 2020;Guo et al, 2022;Gong et al, 2019;Liu et al, 2023;Meng et al 2020;Vierikko & Yli-Pelkonen, 2019;wade et al, 2023;Wu et al, 2019a;Yu et al, 2022;Zhang et al, 2022b;Zingraff-Hamed et al, 2022). Furthermore, two studies also discussed the motivation for restoration (Gargiulo et al, 2020;Jakstis et al, 2023). River proximity is a significant attraction for many individuals, as they prefer to be as close to the wa-Landscape Online 99 (2024) 1121 | ter as possible (Eid et al, 2021), particularly during hot summers, eliciting feelings of relaxation or tranquillity upon encountering water (Ćwik et al, 2021).…”
Section: Personal Attributesmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals visit urban riversides primarily for physical exercise, recreation and leisure, including activities such as walking or jogging, cycling, swimming, dancing, skateboarding, rowing, dragon boat racing, water marathons, dog walking, picnicking, dining, photography, social gatherings, commuting, chess, and camping (e.g., Chen & Ma, 2023;Gargiulo et al, 2020;Guo et al, 2022;Gong et al, 2019;Liu et al, 2023;Meng et al 2020;Vierikko & Yli-Pelkonen, 2019;wade et al, 2023;Wu et al, 2019a;Yu et al, 2022;Zhang et al, 2022b;Zingraff-Hamed et al, 2022). Furthermore, two studies also discussed the motivation for restoration (Gargiulo et al, 2020;Jakstis et al, 2023). River proximity is a significant attraction for many individuals, as they prefer to be as close to the wa-Landscape Online 99 (2024) 1121 | ter as possible (Eid et al, 2021), particularly during hot summers, eliciting feelings of relaxation or tranquillity upon encountering water (Ćwik et al, 2021).…”
Section: Personal Attributesmentioning
confidence: 99%
“…In Finland, it was observed that during the summer season, most visitors resided in rental apartments rather than vacation homes, while non-summer visitors predominantly stayed in their own detached houses (Vierikko & Yli-Pelkonen, 2019). A study encompassing fifteen European countries conducted separate examinations for the Nordic, Central European, and Southern European regions and found variations in the frequency of urban river green space visits before and during the pandemic across the three different regions (Jakstis et al, 2023). Xie et al (2023) indicated a negative correlation between homeownership rate and riverside utilization frequency.…”
Section: Personal Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing urbanization means more pressure is placed on urban landscapes to provide multifunctional benefits. These managed urban landscapes, green spaces built or maintained by humans in urban settings such as sports fields, parks, and even backyards, have seen a significant and sustained increase in usage throughout the course of the COVID‐19 pandemic (Jakstis et al., 2022; Ugolini et al., 2021). Contact with and proximity to urban nature can have important implications for health and well‐being of urban residents and provide important environmental benefits (Groenewegen et al., 2006; Hunter et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of blue and green spaces are important for healthy ecosystems, impacting planetary health (Beninde et al, 2015). The diversity of blue and green spaces also has implications for how children and adults engage with these spaces, and their associated health-related benefits (Georgiou et al, 2021;Jakstis et al, 2023). The animals, plants, smells and experiences people have in these spaces differ, as do people's preferences.…”
Section: Introductionmentioning
confidence: 99%